An investigation into and validation of the shear strength of asphalt mixes as a performance related material property with regard to pavement rutting - Lorio, Renaldo (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1997.